Estabilidade da oclusão tubular de diferentes agentes obliteradores para tratamento de hipersensibilidade dentinária - Moura, Guilherme Faria (2016)
In order to test the stability of dentinal tubules occlusion promoted by tubular front sealing agents to corrosive / abrasive challenges, the aim of our study is to evaluate the occlusion and stability of tubule-occluded products for the treatment of dentin hypersensitivity. Fifty sound tooth were randomly assigned in five groups (n=10), CL: Self Adhesive Sealant (Clinpro XT), TM: Calcium phosphate (Teethmate Desensitizer), GL: Glutaraldehyde (5% Gluma Desensitizer), NP: nano calcium phosphate (Nano P), 5% potassium oxalate (Painless). They were prepared to expose dentinal tubules of the cervical region, just below the cement enamel junction, submitted to treatment and later the challenges with hydrochloric acid and brushing, to simulate oral cavity of patients with gastroesophageal reflux disease (GERD). The analyzes were performed by counting, area and perimeter of the tubules, surface roughness, volume variation, height and angle vertical step, using the laser confocal microscope to evaluate the power of tubule-occluding agents and durability after the acids challenges and brushing. All criteria evaluated were submitted to appropriate statistical analysis. The effectiveness of the tested agents was evidenced in relation to time periods, all groups showed statistical differences between the initial and after treatment stages however only the CL, TM, GL groups did not achieve statistical differences between treatment and post challenge stages, proving stronger. When compared between groups, the CL was the only group that promoted complete obliteration of all dentinal tubules, maintained this obliteration after the challenges, and presents statistics differences in relation to the other groups in all variables. The use of desensitizing agents is effective in dentinal tubule occlusion. The CL, TM, GL agents were more resistant against biocorrosive-erosive challenges; the CL group was group that promoted better tubule obliteration. The surface roughness was higher for the CL group after the challenges.